*Motivational Pathways Underlying Gifted Underachievement: Trajectory Classes, Longitudinal Outcomes, and Predicting Factors. (July 2023) - Ramos, Alicia; Lavrijsen, Jeroen; Linnenbrink-Garcia, Lisa; Soenens, Bart; Vansteenkiste, Maarten; Sypré, Sabine; Boncquet, Michiel; Verschueren, Karine
This study used a longitudinal person-oriented approach to examine whether two distinct developmental pathways of maladaptive motivation could be distinguished among high-ability students (intelligence quotient [IQ] ≥ 120, N = 403, M age = 12.2 years, 60.5% males), as proposed by the Pathways to Underachievement Model. Latent class growth analysis provided evidence for a three-class solution, including an adaptive class and two maladaptive classes, largely corresponding with the predictions of the Pathways to Underachievement Model. Furthermore, the classes related to the outcome variables in the expected ways, with the maladaptive classes showing higher disengagement and underachievement. These findings substantiate the Pathways to Underachievement Model and provide developmental insight into the multiple motivational pathways underlying disengagement and underachievement among high-ability students.